Multiple glutathione-S-transferases detoxify diverse glucosinolate-based defenses of Brassicales plants in a generalist lepidopteran herbivore (Spodoptera littoralis) - Ruo Sun; Samantha Römhild; Yoko Nakamura; Michael Reichelt; Katrin Luck; Duc Tam Mai; Beate Rothe; Jonathan Gershenzon; Daniel Giddings Vassão (Communications Biology)
Abstract Brassicales plants defend themselves with glucosinolates that, upon herbivory, are hydrolyzed into toxic isothiocyanates (ITCs) and other derivatives. The side chain diversity of glucosinolates results in a range of structurally distinct products, but how this chemical variation affects herbivores and their detoxification responses remains incompletely understood. Here, we show the effects of ITC hydrolysis products with various side chains on Spodoptera littoralis larvae and their detoxification system. ITCs inhibit larval growth to varying degrees, depending on the chemical nature of their side chain. The larvae metabolize ITCs by conjugating them to glutathione in the mercapturic acid pathway and to lysine forming an amine conjugate. Over half of the 34 S. littoralis glutathione-S-transferases (GSTs), tested as His-tagged derivatives, actively conjugate ITCs, with most catalyzing reactions with multiple substrates. Larval performance on various ITC-containing diets correlates positively with GST activity, highlighting this detoxification system’s role in supporting growth on glucosinolate-containing plants. The propensity of multiple GSTs to react with an individual ITC and the wide expression of GST-encoding genes across larval organs likely promote the ability of this generalist herbivore to thrive on glucosinolate-defended Brassicales plants. These findings provide insight into herbivore adaptation and may inform future research on plant–insect interactions.